Serum lactate dehydrogenase and rapidly progressive interstitial lung disease are associated with increased mortality in anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis - Wang, Gang; Yan, Dong; Zhang, Yujie; Liu, Chang; Liu, Zhichun (Frontiers in Immunology, 2025)
ObjectiveThis study aims to evaluate the clinical characteristics and prognostic significance of serum lactate dehydrogenase (LDH) in patients with anti-MDA5+ dermatomyositis (anti-MDA5+ DM).MethodsWe assessed 246 consecutive patients with anti-MDA5+ DM. The patients were divided into two groups based on LDH levels: the LDH ≤ 338 U/L group and the LDH > 338 U/L group. We compared the clinical characteristics, laboratory findings, and long-term prognosis between the two groups.ResultsOverall, the one-year mortality rate in patients with anti-MDA5+ DM was high, at 24.39% (60/246). LDH levels exhibited a nonlinear, inverted S-shaped relationship with the overall mortality risk in anti-MDA5+ DM patients (nonlinear P = 0.001). Patients in the LDH > 338 U/L group had significantly higher levels of ALT [64.0 (32.0, 121.0) vs 40.0 (23.0, 66.5), P<0.001], AST [75.0 (47.5, 134.0) vs 40.0 (26.0, 60.6), P<0.001], CK [107.0 (42.0, 208.8) vs 50.0 (35.5, 100.5), P<0.001], CRP [8.5 (3.5, 17.6) vs 4.7 (2.7, 10.2), P<0.001], and serum ferritin levels [1307.6 (679.8, 1565.5) vs 1001.0 (391.2, 1307.6), P<0.001] compared to the LDH ≤ 338 U/L group. Additionally, the positivity rate of Anti-Ro52 antibodies (70.7% vs 57.7%, P = 0.033), the incidence of rapidly progressive interstitial lung disease (RPILD) (42.3% vs 29.3%, P = 0.033), and the mortality rate (35.0% vs 13.8%, P<0.001) were significantly higher in the LDH > 338 U/L group than in the LDH ≤ 338 U/L group. Multivariable regression analysis revealed that LDH > 338 U/L and the presence of RPILD were associated with poor prognosis [hazard ratios of 2.253 (95% CI 1.258, 4.035, P = 0.006) and 10.293 (95% CI 4.683, 22.623, P < 0.001), respectively].ConclusionPatients with different LDH levels exhibit distinct clinical characteristics, laboratory findings, and long-term prognosis. Elevated LDH levels (> 338 U/L) and the presence of RPILD are associated with poor prognosis.